Race and remembrance : a memoir - Johnson, Arthur L., 1925-2011 (African American life series., 2008)
"Race and Remembrance tells the remarkable life story of Arthur L. Johnson, a Detroit civil rights and community leader, educator, and administrator whose career spans much of the last century. In his own words, Johnson takes readers through the arc of his distinguished career, which includes his work with the Detroit branch of the NAACP, the Michigan Civil Rights Commission, and Wayne State University ... Race and Remembrance offers an insider's view into the social factors affecting the lives of African Americans in the twentieth century, making clear the enormous effort and personal sacrifice required in fighting racial discrimination and poverty in Detroit and beyond. Readers interested in African American social history and political organization will appreciate this unique and revealing volume."--Jacket